Training on Sustainable House Design Based on the Utilization of Natural Lighting in Nyogan Village - Ermadani, Ermadani; Febriasti Bahar, Fetty; Suryadri, Hadistya; Galih Prabasari, Ira; Alfernando, Oki (LPPM Universitas Jambi, 2023)
The development of housing has become a government focus, particularly with the introduction of subsidized housing. However, current residential construction often prioritizes financing and aesthetics, neglecting other critical aspects such as environmental conditions and climate factors, including natural lighting and air circulation. Limited public knowledge about these issues contributes to the lack of consideration for natural lighting in home construction. This aspect is vital for creating environmentally friendly homes, as utilizing sunlight can reduce electricity consumption, leading to cost efficiency and environmental sustainability. Therefore, training and outreach are necessary for the community in Nyogan Village, Mestong District, Muaro Jambi Regency, focusing on the use of natural lighting in eco-friendly home design. The existing conditions in Nyogan often result in power outages lasting up to two days, highlighting the need for natural lighting during the day and evening. The training involved local infrastructure officials, carpenters, and community members, providing them with pocket guides on eco-friendly home construction emphasizing natural light utilization. This community service activity has enhanced public knowledge about sustainable housing and increased interest in building environmentally friendly homes.